Polarization independent single-PD coherent ONU receiver with centralized scrambling in udWDM-PONs - Cano, Iván N.; Lerin, Adolfo; Polo, Victor; Prat, Josep (2014 The European Conference on Optical Communication (ECOC), 2014)
A centralized polarization scrambling and single-PD coherent ONU Rx system is proposed and tested with two Tx and direct-phase modulated DFBs. Polarization independence at the Rx, and a sensitivity at BER=10 -3 of ×45dBm with 7.5GHz channel spacing were achieved.